An Analysis of Patient Safety Management by The Hospital Quality Committee: A Case Study on Inpatient Nurses at The Islamic Hospital of Surakarta (2025) - Oktavia, Eka; Salsabila, Hanif; Masdiana Saputri , Zeni (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Patient safety is a critical component in improving the quality of hospital services. However, various patient safety incidents are still occurring due to suboptimal implementation. The Quality Committee plays a strategic role in managing patient safety, including program development, incident investigation, reporting, and evaluation. This study aims to analyze patient safety management by the Quality Committee, focusing on inpatient nursing services at Rumah Sakit Islam Surakarta. Method: This research employed a qualitative approach with a phenomenological method. Data were collected through in-depth interviews with six inpatient nurses and direct field observations. Thematic analysis was conducted through data reduction, data presentation, and conclusion drawing. Result: The findings indicate that the implementation of patient safety management by the Quality Committee has not been fully optimized. Key obstacles include underreporting of incidents, limited staff understanding of standard operating procedures (SOPs), lack of regular education and training, and weak documentation and coordination systems. The committee’s role has not yet fully integrated the functions of planning, organizing, implementing, and controlling in the context of patient safety. Conclusion: Patient safety management at Rumah Sakit Islam Surakarta requires strengthening in terms of system structure, safety culture, and active nurse involvement. Stronger leadership support, enhanced human resource capacity, and optimal performance of the Quality Committee are essential to establish a structured and sustainable patient safety system.